Designing Authenticated Key Management Scheme in 6G-Enabled Network in a Box Deployed for Industrial Applications - Wazid, Mohammad; Das, Ashok Kumar; Kumar, Neeraj; Alazab, Mamoun (IEEE transactions on industrial informatics, 2021)
6G-enabled network in a box (NIB) is a multigenerational, rapidly deployable hardware, and software technology for the communication. 6G-enabled NIB provides high level of flexibility which makes it capable to provide connectivity services for different types of applications as it is effective for the communications of after disaster scenario, battlefields scenario, and industrial scenario. In 6G-enabled NIB deployed industrial applications, various passive and active attacks are possible because the involved entities communicate over insecure channel. In this article, a new remote user authentication and key management scheme is proposed for securing 6G-enabled NIB deployed for industrial applications, which we call in short as UAKMS-NIB. The security analysis shows the resilience of UAKMS-NIB against various types of possible attacks. The practical demonstration of UAKMS-NIB is also provided to measure its impact on the network performance parameters. Finally, a comparative analysis with other closely related existing schemes shows that UAKMS-NIB performs better than the existing schemes.